2003
DOI: 10.1137/s009753970139450x
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Subgroup Problem and Quantum Computation Using Group Representations

Abstract: The hidden subgroup problem is the foundation of many quantum algorithms. An efficient solution is known for the problem over abelian groups, employed by both Simon's algorithm and Shor's factoring and discrete log algorithms. The nonabelian case, however, remains open; an efficient solution would give rise to an efficient quantum algorithm for graph isomorphism. We fully analyze a natural generalization of the algorithm for the abelian case to the nonabelian case and show that the algorithm determines the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 23 publications
(24 reference statements)
0
77
0
Order By: Relevance
“…[HRTS03,GSVV04] show that O(log |G|) weak Fourier samplings suffice to reconstruct the normal core c(H) of the hidden subgroup H, where c(H) is the largest normal subgroup of G contained in H. Adapting their arguments, we prove the following result. …”
Section: Hidden Subgroup Problem and Fourier Samplingmentioning
confidence: 83%
See 1 more Smart Citation
“…[HRTS03,GSVV04] show that O(log |G|) weak Fourier samplings suffice to reconstruct the normal core c(H) of the hidden subgroup H, where c(H) is the largest normal subgroup of G contained in H. Adapting their arguments, we prove the following result. …”
Section: Hidden Subgroup Problem and Fourier Samplingmentioning
confidence: 83%
“…Hallgren, Russell and Ta-Shma [HRTS03] showed that polynomially many iterations of weak Fourier sampling give enough information to reconstruct normal hidden subgroups. More generally, they show that the normal core c(H) of the hidden subgroup H (i. e. the largest normal subgroup of G contained in H) can be reconstructed via the weak method.…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, it is possible to formulate the GI problems in terms as in (4). The formula can be translated into the following potential Hamiltonian: …”
Section: Adiabatic Quantum Walkmentioning
confidence: 99%
“…GI possesses peculiar features that make it an interesting candidate for an efficient quantum algorithm. In fact it is in NP but is not believed to be NP-Complete: like factoring, it belongs to the NP-Intermediate family [2] and is representative of the (non-Abelian) hidden subgroup problem family [3][4][5]. The best classical general algorithm solves GI for graphs of n vertices in time O(c √ n log n ), were c is a constant.…”
Section: Introductionmentioning
confidence: 99%
“…• Since the subgroups j Stab are not normal subgroups of N S , it follows from the work of Hallgren et al [55,56] that the standard non-abelian hidden subgroup algorithm will find the largest normal subgroup of N S lying in Moreover, one can not hope to use this QHS approach to Grover's algorithm to find a faster quantum algorithm. For Zalka [77] has shown that Grover's algorithm is optimal.…”
Section: Iia10 Is Grover's Algorithm a Qhs Algorithm?mentioning
confidence: 99%